Why votes have a value - Ingolf Dittmann; Dorothea Kübler; Ernst Maug; Lydia Mechtenberg (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2007)
We perform an experiment where subjects pay for the right to participate in a shareholder vote. We find that experimental subjects are willing to pay a significant premium for the voting right even though there should be no such premium in our setup under full rationality. Private benefits from controlling the firm are absent from our setup and overconfidence cannot explain the size of the observed voting premium. The premium disappears in treatments where voting has no material consequences for the subjects. We conclude that individuals enjoy being part of a group that exercises power and are therefore willing to pay for the right to vote even when the impact of their own vote on their payoffs is negligible.
Keywords: C92; D72; G32; 330; Voting; dual-class shares; paradox of voting; experimental economics; Stimmrecht (Gesellschaftsrecht); Willingness to pay; Abstimmungsparadoxon; Test